Assessing water governance challenges in the lake Urmia Basin, Iran: a DPSIR-based approach - Haji, Latif; Fallah Haghighi, Negin (Frontiers in Environmental Science, 2026)
The intensifying water crisis in the Lake Urmia Basin, Iran, is driven by climate change and human activities, highlighting the need to examine the economic, social, and management factors affecting water resources. This study analyzes agricultural water governance in the basin, which exemplifies broader governance challenges in Iran. Using the Driver-Pressure-State-Impact-Response framework, the research systematically assesses the current water governance status. The analysis is further enhanced through Partial Least Squares-Structural Equation Modeling (PLS-SEM), providing insights into the interconnections among governance components. A mixed-methods approach, combining quantitative surveys and qualitative semi-structured interviews, offers a comprehensive understanding of the governance landscape. Qualitative results identified 10 “driver” indicators (D) of poor governance, nine “pressure” indicators (P), seven “state” indicators (S), 13 “impact” indicators (I), and 16 “response” indicators (R). Quantitative analysis revealed that drivers significantly contribute to the escalation of the water crisis. Addressing these drivers, mitigating pressures, improving the current undesirable state, and managing the negative impacts of inadequate water governance are strongly influenced by comprehensive responses. This study highlights the complexities of water governance assessment and the dynamic interactions among its components. The findings provide an evidence-based roadmap for designing practical short- and long-term interventions to improve water governance in the Lake Urmia Basin and similar contexts across Iran.